BIOCONVERSION OF COPRA MEAL INTO PREBIOTIC MANNOOLIGOSACCHARIDES USING ENDO-β-1,4-MANNANASE PRODUCING BY ASPERGILLUS NIGER BK 01 - Cương, Đỗ Biên; Hoa, Nguyễn Thị; Huyền, Lê Thị; Thu, Đặng Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARYMannooligosaccharides (MOS) are among the excellent prebiotics which recently gained great interest. These compounds are produced from various raw materials based on hydrolysis action of mannanases. Our aim was to investigate appropriate conditions to bioconvert the copra meal, a ground product of extraction residue of coconut oil harvested in Hoai Nhon (Binh Dinh, Vietnam) into MOS. A trial of MOS production was conducted at laboratory scale. The right conditions shown in this study were: substrate concentration, 10% (w/v); initial pH, 6.0; temperature, 40oC; reaction time, 16 h; native or recombinant Aspergillus niger BK01 endo-β-1,4-mannanase, 40 U/g-dry solid. Analysis of oligosaccharide products obtained during these enzymatic hydrolysis revealed that the raw recombinant mannanase from A.niger might yield MOS with higher purity than that of hydrolysis using native one. The hydrolysates contained mannobiose and mannotriose as main products.